Analisa Jembatan Garam untuk Meningkatkan Kestabilan Termal Enzim Xilanase Aspergillus niger - Nya Daniaty Malau; Manogari Sianturi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2017)
Enzymes are the same biomolecules such as proteins, has only a functional difference. Enzymes are biocatalyst that recently applied to many industrial fields. To be applied in the field of industrial enzymes should be enhanced stability against temperature. Analysis of the salt bridge is able to demonstrate the potential of residues mutated to improve thermal stability. Molecular dynamics simulations performed by observing the unfolding process. Variations in temperature used is 400 K, 450 K and 500 K, respectively performed for 2.5 ns. Then analyzed the pair a salt bridge is formed. There are 25 pairs of salt bridges at a temperature of 400 K, 24 pairs of salt bridges at a temperature of 450 K, and there are 30 pairs of the salt bridge is formed at a temperature of 500 K. To determine the salt bridge partner is a key enzyme kesstabilan we then plotted salt bridge between distances (Ã… ) with time (ns) only at a temperature of 500 K, for allegedly at these temperatures has been a process of unfolding. Of the 30 pairs of the salt bridge that had plotted the distance with time, the pair obtained a salt bridge that pattern similar to the pattern chart graph analysis Root-mean-square deviation (RMSD). There are three curves salt bridge that pattern is similar to the pattern of RMSD curve and SASA, namely the salt bridge Glu84-Arg134, Asp104-Arg134 and Asp113-Arg115. The sharp rise in the value of RMSD and the resulting rupture SASA three pairs of the salt bridges. So when carried mutations in-silico candidate mutants that will be transferred is the amino acid residues are thought to play a role in electrostatic interactions and replace it with another amino acid residue on the basis of structural similarities. Keywords: Salt bridge, Electrostatic bond, Mutation, Unfolding